Authenticity, Interactivity, and Collaboration in VR Learning Games - Thompson, Meredith M.; Wang, Annie; Roy, Dan; Klopfer, Eric (Frontiers in Robotics and AI, 2018)
Decreasing cost and increasing technology access in schools places 3D immersive virtual reality (VR) within the reach of K-12 classrooms (Korbey, 2017). Educators have great interest in incorporating VR into classrooms because they are engaging and often novel experiences. However, long-term curriculum development must be positioned on how to best leverage the unique affordances of VR, be informed by theory and research, and integrate VR in meaningful ways that continue to motivate students even after experiences are no longer novel. We propose the theoretical framework of embodied learning and discuss how VR and reflect on current research findings to outline effective applications of VR for guidelines in developing educational materials using those tools. We discuss two particular examples: spatial awareness and collaboration. We share our perspectives on the benefits and challenges of applying these principles in a learning game about cellular biology.